Improvement of Radioimmunotherapy Using Pretargeting - Frampas, Eric; Rousseau, Caroline; Bodet-Milin, Caroline; Barbet, Jacques; Chatal, Jean-Francois; Kraeber-Bodéré, Françoise (Frontiers in Oncology, 2013)
During the past two decades, considerable research has been devoted to radionuclide therapy using radiolabelled monoclonal antibodies and receptor binding agents. Conventional Radioimmunotherapy (RIT) is now an established and important tool in the treatment of hematologic malignancies such as Non-Hodgkin lymphoma. For solid malignancies, the efficacy of RIT has not been as successful due to lower radiosensitivity, difficult penetration of the antibody into the tumor and potential excessive radiation to normal tissues. Innovative approaches have been developed in order to enhance tumor absorbed dose while limiting toxicity to overcome the different limitations due to the tumor and host characteristics. Pretargeting techniques (pRIT) are a promising approach that consists of decoupling the delivery of a tumor monoclonal antibody (mAb) from the delivery of the radionuclide. This results in a much higher tumor-to-normal tissue ratio and is favorable for therapy as well and imaging. This includes various strategies based on avidin/streptavidin-biotin, DNA-complementary DNA and bispecific antibody-hapten bindings. PRIT continuously evolves with the investigation of new molecular constructs and the development of radiochemistry. Pharmacokinetics improve dosimetry depending on the radionuclides used (alpha, beta and Auger emitters) with prediction of tumor response and host toxicities. New constructs such as the Dock and Lock technology allow production of a variety of mABs directed against tumor-associated antigens. Survival benefit has already been shown in medullary thyroid carcinoma. Improvement in delivery of radioactivity to tumors with these pretargeting procedures associated with reduced hematologic toxicity will become the next generation of RIT. The following review addresses actual technical and clinical considerations and future development of pRIT.